Enhancing Laptop Security Policy using RiskIT Framework - Wijaya, Andy; Soetomo, Mohammad Amin (Journal of Applied Information, Communication and Technology, 2018)
The usage of laptop as replacement of PC for staff mobility has been continuing to increase for many companies. In the same time the threats related to the use of laptops has evolving due to technology and internet growth. To protect the corporate information, the policy of the laptop is become mandatory to continuously reviewed and enhanced. This paper explains the enhancement of laptop security policies. ISACA Risk IT Framework is used as the methodology. It is expected that the latest security risks (from social engineering to cyber risk) facing by the company are mitigated. New set of policies are suggested. It covers process, people and technology.